Rice Diversity of Inpari IR Nutri Zinc Variety in Three Clanning Seasons in West Nusa Tenggara - Hiryana Windiyani; Baiq Tri Ratna Erawati (Jurnal Biologi Tropis, 2023)
The spread of the Corona virus (Covid 19) is still developing with new variants, Indonesia is one of the countries that currently has not been able to overcome the pandemic. One of the ways to maintain the immune system is by maintaining nutritious food intake and consuming healthy foods. Deficiency of Zn in the body results in decreased endurance, productivity, and human quality of life. Zn deficiency is one of the causes of stunting. Inpari IR Nutri Zinc is biofortified rice with a zinc content of 34.51 ppm which plays a role in preventing stunting, helping to increase nutritional value while overcoming iron deficiency in the community. Based on the superiority of Inpari IR Nutri Zinc rice, it is necessary to study the productivity and suitability of agro-ecosystems on Lombok Island. The study was carried out in three locations, three growing seasons using Standard Operating Procedures (SOP) for IR Nutri Zinc Inpari Rice Cultivation. The three locations are Mataram District at MT I/2020, Gerung District MT II/2020 and Narmada District MT III/2020. The study was carried out using a Randomized Block Design (RBD) design in 3 locations, 3 growing seasons using the Standard Operating Procedure (SOP) for IR Nutri Zinc Inpari Rice Cultivation. The aim of the study was to determine the level of productivity consistency of the Inpari IR Nutri Zinc variety using the Standard Operating Procedure (SOP) for rice cultivation at the 3 locations. The planting of Inpari IR Nutri Zinc rice at each location and growing season was repeated 5 times. Parameters observed included agronomic growth and productivity. Data collection consists of secondary data (rainfall data) and primary data. For primary data carried out by direct observation in the field and interviews with implementing farmers and business actors. Inpari IR Nutri Zinc planted in 3 locations using standard operating procedures (SOP) for rice cultivation, showed higher productivity than the average yield of Inpari IR Nutri Zinc at the national level. The productivity of rice planted in the Mataram sub-district in MH 2020 was 7.63 t/ha. The planting of Inpari IR Nutri Zinc rice is suitable for planting in the rainy season, but can produce well in the dry season with water conditions or an average rainfall of at least 100 mm / growing season. Rice Inpari Nutri Zinc can and should be developed in West Nusa Tenggara Province, especially in paddy fields and districts where the stunting rate is still quite high in an effort to reduce and prevent stunting in West Nusa Tenggara.